2022
DOI: 10.3390/vaccines10091569
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and Safety of COVID-19 Vaccines among People Living with HIV: A Systematic Review and Meta-Analysis

Abstract: Background: The immunogenicity and safety of COVID-19 vaccines among people living with human immunodeficiency virus (PLWH) are unclear. We aimed to evaluate the immunogenicity and safety of COVID-19 vaccines among PLWH. Methods: We systematically searched PubMed, EMBASE, and Web of Science from 1 January 2020 to 28 April 2022 and included observational studies, randomized clinal trials, and non-randomized clinical trials reporting extractable data about the immunogenicity and safety of COVID-19 vaccines among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 67 publications
2
14
0
Order By: Relevance
“…It is worth noting that this pooled median antibody response following mRNA vaccination in PLWH can be used to compare with the concentrations of antibodies in the general population after COVID‐19 vaccination. Kang et al in a systematic review and meta‐analysis evaluated the immunogenicity of different vaccines against COVID‐19 among PLWH and demonstrated compatible seroconversion of COVID‐19 vaccines between PLWH and healthy individuals after the second dose 34 . Also in their study the GMT of antibody showed no significant difference among PLWH and controls which is similar with our findings.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It is worth noting that this pooled median antibody response following mRNA vaccination in PLWH can be used to compare with the concentrations of antibodies in the general population after COVID‐19 vaccination. Kang et al in a systematic review and meta‐analysis evaluated the immunogenicity of different vaccines against COVID‐19 among PLWH and demonstrated compatible seroconversion of COVID‐19 vaccines between PLWH and healthy individuals after the second dose 34 . Also in their study the GMT of antibody showed no significant difference among PLWH and controls which is similar with our findings.…”
Section: Discussionsupporting
confidence: 90%
“…There are several studies and a meta‐analysis that demonstrated the immunogenicity and safety of different SARS‐CoV‐2 vaccines among PLWH 33–36 . However, humoral responses to the two doses schedule of mRNA‐based vaccines in individuals with well‐controlled HIV infection remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the above-mentioned studies correspond with the results of three meta-analyses [26 ▪ ,27,28]. In the first meta-analysis, a total of 34 eligible studies covering 4517 PLWH were included.…”
Section: Safety and Immunogenicity Of Covid 19 Vaccines In People Liv...mentioning
confidence: 56%
“…Among 14 study results, [19][20][21][22][23][24][25][26][27][28][29][30][31][32] there was acceptable for immunogenicity, a key response for the development of a vaccinationinduced immunogenicity both humoral and cellular immunity 2 or 3 doses of vaccination) 19 and acceptable safety in 11 studies (78.57 %). Acceptable potent immunogenicity was found in patients aged more than 40 years with chronic diseases, particularly, chronic respiratory diseases and coronary artery diseases.…”
Section: Discussionmentioning
confidence: 99%
“…20 Pooled seroconversion rate in people living with HIV (PLWH) after the first and second doses were 67.51 and 96.65 %, respectively. 21 In lung-cancer patients, number of doses (third dose, etc.) and intervals of mRNA-COVID-19 vaccination are suggested to maintain effective immunity.…”
Section: Discussionmentioning
confidence: 99%